PHYTOCEMICAL ANALYSIS AND ANTI OKSIDANT ACTIVITY OF THE WOOD ETHANOLIC EXTRACTS OF SIRIH HUTAN (Pipe aduncum) - Erwin Erwin (Jurnal Akta Kimia Indonesia (Indonesia Chimica Acta), 2015)
Sirih hutan (Piper aduncum) grew evenly in the tropical rain forests of East Kalimantan; it was used as a drug itching by local people. The present study is aimed to determine the chemical content and evaluate the free radical scavenging potential antioxidant activity of the extract of Sirih hutan wood. Based on the results of the GC-MS of the wood extract of Sirih hutan consists of 11 compounds. The inhibition of DPPH scavenging free radicalst of extract in ethanol preparations is IC50 259.74 ppm.